Differentiated Learning Innovation Training in Malaka Regency : Integrating Technology and Local Wisdom - Yantus A.B. Neolaka; Jasman; Kasimir Sarifudin; Sudirman; Klaudia Ensriana Norlasty Bambut; Daud Dakabesi (Jurnal Dremi (Demi Pengabdi Masyarakat), 2025)
The differentiated learning innovation training in Malaka Regency involved 50 teachers to enhance their competencies in developing strategies responsive to students’ needs and local contexts. The training focused on three aspects: understanding differentiated learning, utilizing Google Sites, and integrating local wisdom, delivered through lectures, practice, and mentoring. Evaluation results indicated significant improvements: technology use increased by 94.4%, local wisdom integration by 72.7%, and understanding of differentiated learning by 66.7%. Participants’ satisfaction was rated very high, with average scores above 4.5 across materials, methods, facilitators, and instructional media. These findings demonstrate that the training effectively strengthened teachers’ pedagogical capacity while providing a sustainable professional development model to improve learning quality in Malaka Regency